Ethnic Comparison of Attitudes and Beliefs About Cigarette Smoking - Pérez-Stable, Eliseo J (Blackwell Science Inc, 1998)
OBJECTIVE: To determine if hypothesized differences in attitudes and beliefs about cigarette smoking between Latino and non-Latino white smokers are independent of years of formal education and number of cigarettes smoked per day. DESIGN: Cross-sectional survey using a random digit dial telephone method. SETTING: San Francisco census tracts with at least 10% Latinos in the 1990 Census. PARTICIPANTS: Three hundred twelve Latinos (198 men and 114 women) and 354 non-Latino whites (186 men and 168 women), 18 to 65 years of age, who were current cigarette smokers participated. MEASUREMENTS AND MAIN RESULTS: Self-reports of cigarette smoking behavior, antecedents to smoking, reasons to quit smoking, and reasons to continue smoking were the measures. Latino smokers were younger (36.6 vs 39.6 years, p < .01), had fewer years of education (11.0 vs 14.3 years, p < .001), and smoked on average fewer cigarettes per day (9.7 vs 20.1, p < .001). Compared with whites, Latino smokers were less likely to report smoking “almost always or often” after 13 of 17 antecedents (each p < .001), and more likely to consider it important to quit for 12 of 15 reasons (each p < .001). In multivariate analyses after adjusting for gender, age, education, income, and number of cigarettes smoked per day, Latino ethnicity was a significant predictor of being less likely to smoke while talking on the telephone (odds ratio [OR] 0.41; 95% confidence interval [CI] 0.26, 0.64), drinking alcoholic beverages (OR 0.66; 95% CI 0.44, 0.99), after eating (OR 0.55, 95% CI 0.37, 0.81), or at a bar (OR 0.62, 95% CI 0.41, 0.94), and a significant predictor of being more likely to smoke at a party (OR 1.72; 95% CI 1.14, 2.60). Latino ethnicity was a significant predictor of considering quitting important because of being criticized by family (OR 1.93; 95% CI 1.26, 2.98), burning clothes (OR 1.57; 95% CI 1.02, 2.42), damaging children's health (OR 1.67; 95% CI 1.08, 2.57), bad breath (OR 2.07; 95% CI 1.40, 3.06), family pressure (OR 1.67; 95% CI 1.10, 2.60), and being a good example to children (OR 1.83; 95% CI 1.21, 2.76). CONCLUSIONS: Differences in attitudes and beliefs about cigarette smoking between Latinos and whites are independent of education and number of cigarettes smoked. We recommend that these ethnic differences be incorporated into smoking cessation interventions for Latino smokers.